1981
DOI: 10.1143/jjap.20.2057
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of Dielectric Breakdown in Liquid Nitrogen

Abstract: Breakdown voltage characteristics in liquid nitrogen (liq.N2) have been studied in the pressure range between 1 and 15 atm. For constant gap length, the breakdown voltage increases with increasing pressure and saturates at around 10 atm. For shorter pulse width, the increase in breakdown voltage with pressure becomes less remarkable. In a non-uniform field of a plane-needle electrodes system, the breakdown voltage of the negative needle configuration increases remarkably with increasing pressure but that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We found that the breakdown strength for anode-initiated breakdown in a 200 µm gap was reduced by half when the pressure was reduced from atmospheric pressure to 16 Torr [96]. Similar results were obtained for hydrocarbon liquids and for liquid gases [97,98]. A strong pressure dependence was also observed in non-polar liquids, for example, by Krasucki in hexchlorodiphenol, while Bonifaci disputed a strong pressure dependence, at least for liquid noble gases such as argon [54,99].…”
Section: Hydrostatic Pressurementioning
confidence: 54%
“…We found that the breakdown strength for anode-initiated breakdown in a 200 µm gap was reduced by half when the pressure was reduced from atmospheric pressure to 16 Torr [96]. Similar results were obtained for hydrocarbon liquids and for liquid gases [97,98]. A strong pressure dependence was also observed in non-polar liquids, for example, by Krasucki in hexchlorodiphenol, while Bonifaci disputed a strong pressure dependence, at least for liquid noble gases such as argon [54,99].…”
Section: Hydrostatic Pressurementioning
confidence: 54%
“…Therefore, the strength of the liquid breakdown field will also be increased. 28,29 From this point, LNG as an insulating medium has more practical significance.…”
Section: Experimental Results Analysis and Discussionmentioning
confidence: 99%
“…That is to say, for the gas above the liquid level, the increase in pressure is beneficial to restrain the formation of bubbles. Therefore, the strength of the liquid breakdown field will also be increased. , From this point, LNG as an insulating medium has more practical significance.…”
Section: Experimental Results Analysis and Discussionmentioning
confidence: 99%
“…Electrical breakdown strength in liquid nitrogen has been widely studied and data exist for a range of pressures and geometries [8,9]. The volume and area dependence of liquid nitrogen breakdown strength have also been explored [10,11].…”
Section: Introductionmentioning
confidence: 99%